Taiwan’s Politics in Pixels: Analyzing the Democratic Progressive Party’s Digital Rhetoric - Lu, Yipei (Journal of Theory and Practice of Social Science, 2023)
Over seven decades of political stalemate, Taiwan's sovereign status vis-à-vis Mainland China remains an unresolved and volatile issue. The 21st century has witnessed spiraling cross-Strait tensions due to pro-independence endeavors by the Taiwanese Democratic Progressive Party (DPP), challenging the fundamental One China Principle. This delicate equilibrium has experienced further strain by the DPP's employment of digital campaigns to influence Taiwanese citizens' perceptions of Mainland China, while simultaneously bolstering ties with the US in support of autonomy. Amid this complex landscape, media and political propagandas have surfaced as the DPP's prominent instruments to sway its citizenry. However, the potency of digital media in sculpting public opinion and steering political discourse is met with a scarcity of research exploring the DPP's methodologies in advocating for an autonomous Taiwan. To address this gap, this paper offers a preliminary outlook by analyzing the DPP's deployment of digital media and political rhetoric as influential mechanisms to shape its citizens' perceptions of identity.